2019
DOI: 10.29320/sjnpgrj.3.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Image Processing for the Detection of Diabetic Retinopathy and Diabetic Macular Edema

Abstract: Diabetic retinopathy (DR) and diabetic macular edema (DME) are common microvascular retinal diseases in patients with diabetes. The diabetic patients may have a sudden and devastating impact on visual acuity, in the long run leading to blindness. Advanced stages of DR are characterized by the growth of abnormal retinal blood vessels secondary to ischemia. These blood vessels grow in an attempt to supply oxygenated blood to the hypoxic retina. At any time during the progression of DR, patients with diabetes can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Kaggle data set provided retinal images for five severity levels of DR, which are used in a few studies including [23,28]. It is shown in the literature review that many researchers [14][15][16][17][18][19][20][21][22][23][24][25] have devoted their efforts for the detection of the stages of DR. Detection of five stages of DR was proposed in [23] using Kaggle data set and CNN and in [22] through visual features and deep NN using private data collected from a local hospital.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kaggle data set provided retinal images for five severity levels of DR, which are used in a few studies including [23,28]. It is shown in the literature review that many researchers [14][15][16][17][18][19][20][21][22][23][24][25] have devoted their efforts for the detection of the stages of DR. Detection of five stages of DR was proposed in [23] using Kaggle data set and CNN and in [22] through visual features and deep NN using private data collected from a local hospital.…”
Section: Discussionmentioning
confidence: 99%
“…DR lesions can appear anywhere in the retina and this complication makes the detection of five DR-levels a difficult and tedious task for ophthalmologists and hence motivates researchers to design efficient CAD systems. Literature revealed that many researchers proposed efficient methods [8][9][10][11][12][13] for DR-lesion detection and CAD systems [14][15][16][17][18][19][20][21][22][23][24][25] for identification of severity levels of DR. Some of these studies proposed the automated methods to detect severity of DR on the basis of DR-lesions which is quite similar to the one usually practiced by ophthalmologists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation